2006
DOI: 10.1289/ehp.8085
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Immune Toxicity of Depleted Uranium: Effects on Murine Macrophages, CD4 + T Cells, and Gene Expression Profiles

Abstract: Depleted uranium (DU) is a by-product of the uranium enrichment process and shares chemical properties with natural and enriched uranium. To investigate the toxic effects of environmental DU exposure on the immune system, we examined the influences of DU (in the form of uranyl nitrate) on viability and immune function as well as cytokine gene expression in murine peritoneal macrophages and splenic CD4+ T cells. Macrophages and CD4+ T cells were exposed to various concentrations of DU, and cell death via apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 57 publications
1
30
1
1
Order By: Relevance
“…Mouse peritoneal elicited macrophages and splenic CD4 + T cells were prepared exactly according to the method described by Wan et al (2006). The resulting macrophage and T cell purities were all >95%, as determined by CD11b and CD4 staining analyses.…”
Section: Cell Preparations and Pbde Exposurementioning
confidence: 99%
“…Mouse peritoneal elicited macrophages and splenic CD4 + T cells were prepared exactly according to the method described by Wan et al (2006). The resulting macrophage and T cell purities were all >95%, as determined by CD11b and CD4 staining analyses.…”
Section: Cell Preparations and Pbde Exposurementioning
confidence: 99%
“…The cytotoxicity of DU in studies performed in vitro with different cell lines and types varies from doses of 200 to 800 µM (Mirto et al 1999;Carrière et al 2004;Wan et al 2006). NRK-52 E cells undergo death by apoptosis after exposure to low doses of DU.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies, performed in rats and mice, demonstrated that DU alters gene expression, particularly of genes involved in apoptosis (Taulan et al 2004;Monleau et al 2006;Wan et al 2006). In human renal cells, the expression of genes related to apoptosis was also reported to be altered after exposure to DU (Prat et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies and toxicological tests on laboratory animals point to it as being immunotoxic [Wan et al, 2006], teratogenic [Arfsten et al, 2001], neurotoxic [Briner and Murray, 2005], with carcinogenic and leukemogenic potential [Miller et al, 2005]. A 2005 report by epidemiologists concluded: "the human epidemiological evidence is consistent with increased risk of birth defects in offspring of persons exposed to DU."…”
Section: Chemical Toxicity Of Dumentioning
confidence: 99%